An insight into the pasting properties and gel strength of starches from different sources: effect of starch concentration - Castanha, Nanci (2021)
This work aims to evaluate the starch/water concentrations (3.6%, 7.1%, 10.7% and 14.3%) effect of different commercial starch sources (namely cassava, maize, high-amylose maize, waxy maize and potato) regarding their pasting properties by using a Rapid Visco Analyser (RVA), gel strength, and intrinsic characteristics (such as morphology, granules size and distribution). The results showed that the 10.7% concentration (standard concentration usually used for evaluating starch properties) is not always predictive for the starches rheological behaviour. Meanwhile, the characteristics of the formed gels were not only related to RVA properties. For instance, decisions based on the results using the concentration of 10.7% can be far different from those used in industrial applications. The data reported can be useful to demonstrate how conditions, properties and starches characteristics are correlated, also to facilitate the selection of the best conditions that are closer to the desired application.